Educational Resources and the Development of Private Secondary School Education in Oyo State, Nigeria from 1999 to2015 - Abolade, S. B.; Oyelade, A. F. (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
This paper examines educational resources in the development of private secondary school education in Oyo State, Nigeria, between 1999 and 2015. This is with the view to examine the development of private secondary school education in Oyo State, Nigeria, between 1999 and 2015 in historical perspective. In the process it considers development of privately owned secondary schools in the light of adequacy of human and material resources (i.e, teachers and educational facilities) and how these had enhanced the performance of students in the Senior School Certificate Examinations (SSCE) between 1999 and 2015. The study used historical research method, relying on primary and secondary sources of data. The sample consisted of 300 respondents purposively sampled from 60 private secondary schools. Two instruments, â€œQuestionnaire on Adequacy of Educational Resources in Private Secondary Schoolsâ€ (QAERPSS) and â€œStructured Open-ended Interview Scheduleâ€ (SOIS) were used to collect data for the study. The questionnaire had reliability index of 0.73. Periodic and thematic approaches of historical analysis were used to analyse the qualitative data while the percentage was used to analyse the quantitative data. It was found that private secondary schools in Oyo State had adequately qualified teachers and appreciable quantity of modern educational facilities, which contributed to the development of private secondary school education during the period. It is therefore recommended that government at all levels and school proprietors should strive to ensure that the quality of education in public and private secondary schools in Oyo state, Nigeria, remains encouraging. Keywords: Historical research, educational resources, development, private secondary schools, Nigeria.